2023
DOI: 10.3390/jof9020222
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Aspergillus fumigatus to Klebsiella pneumoniae Culture Filtrate Inhibits Growth and Stimulates Gliotoxin Production

Abstract: Aspergillus fumigatus is an opportunistic fungal pathogen capable of inducing chronic and acute infection in susceptible patients. A. fumigatus interacts with numerous bacteria that compose the microbiota of the lung, including Pseudomonas aeruginosa and Klebsiella pneumoniae, both of which are common isolates from cystic fibrosis sputum. Exposure of A. fumigatus to K. pneumoniae culture filtrate reduced fungal growth and increased gliotoxin production. Qualitative proteomic analysis of the K. pneumoniae cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Prior in vitro and some in vivo laboratory studies focusing on the interplay between GNRs and Aspergillus species revealed pleiotropic (synergistic, neutral, or antagonistic) interactions that mediate interspecies competition between molds and GNR [6]. These interactions can result in altered fungal growth, viability, biofilm formation, toxin production, and invasive capacity [6,7]. Mechanistic determinants of inter-kingdom interplay include competition for nutrients and iron (e.g., through the production of siderophores) [8,9], secreted proteins [10], and the release of volatile compounds [11].…”
Section: Introductionmentioning
confidence: 99%
“…Prior in vitro and some in vivo laboratory studies focusing on the interplay between GNRs and Aspergillus species revealed pleiotropic (synergistic, neutral, or antagonistic) interactions that mediate interspecies competition between molds and GNR [6]. These interactions can result in altered fungal growth, viability, biofilm formation, toxin production, and invasive capacity [6,7]. Mechanistic determinants of inter-kingdom interplay include competition for nutrients and iron (e.g., through the production of siderophores) [8,9], secreted proteins [10], and the release of volatile compounds [11].…”
Section: Introductionmentioning
confidence: 99%